Assessing the relationship between business strategy and knowledge acquisition in Polish Manufacturing Enterprises - Patalas-Maliszewska, Justyna (Managerial Economics, 2016)
This study analyzes the interplay between the characteristics of business strategy implementations and their interaction with different types of knowledge in the manufacturing enterprise. It is based on a survey and data obtained from 119 Polish manufacturing enterprises. This study is innovative in applying the Group Method of Data Handling to the business context. This article develops a framework of achieving the strategy’s goals in terms of the types of knowledge acquisition in a manufacturing company, and further discusses the research results.